Relasi Ekonomi Pedagang Hindu di Bandar Dagang Sriwijaya - Fatimah, Siti; Hudaidah, Hudaidah; Jaenudin, Riswan; Lestari, Dea (Jurnal Penelitian Agama Hindu, 2024)
This research focuses on the economic relations of Hindu traders in Sriwijaya trading ports in the VII-XII centuries AD. The problems that will be analyzed are what are the forms of economic relations between Hindu traders in Sriwijaya trading bookies, what is the evidence of the existence of economic relations between Hindu traders in Sriwijaya bookies. The method in this research is the historical research method which consists of searching for primary data, namely observing Sriwijaya artifacts at the Sriwijaya Tourism Park Museum. Carrying out verification of both external and internal criticism, data analysis in the form of interpretation and historical writing. The aim of this research is to explain the economy of Hindu traders in trading houses during the Sriwijaya era in the VII-XII century AD. Based on the results of this research, trade relations have been established between Hindu traders from India in the city of Sriwijaya. This trade relationship is proven by the discovery of artefacts originating from India, such as the discovery of several Hindu statues such as Shiva and Vishnu in Indian style and Hindu temples in the interior of Sriwijaya. Economic relations occur in the form of economic interactions both in the form of buying and selling or bartering merchandise. The establishment of trade relations between Hindu traders and Srivijaya had an impact on the development of Hinduism in the hinterland (Uluan) of Sriwijaya based on archaeological findings in Kapur City, Angsoko, Lesung Batu and Bumiayu. This research provides new findings that in Sriwijaya not only did Buddhism develop but Hinduism also developed, especially in the interior areas of Sriwijaya.